2021
DOI: 10.1177/23996544211019754
|View full text |Cite
|
Sign up to set email alerts
|

Aversive racism and community-instigated policing: The spatial politics of Nextdoor

Abstract: I bring an understanding of the concept and practice of “aversive racism” to scholarly thinking about community formation. I argue that the exclusionary contours of community are in part a product of racialized in- and outgrouping from which people’s capacities for place-making are judged and localized policing is instigated. In bringing these concepts, formations, and practices together, this paper contributes to how urbanists might continue to think about the role of race in displacement, particularly as it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…This "third way" of social service delivery through grassroots organizing [15] is enticing because it potentially shifts the "burden" of care away from social policy and saves public monies [16] (p. 2139). The rise of apps for neighborhood social networks like Nextdoor in the UK and USA during COVID-19 [17] pointed to its plausibility but also showed that structures for inclusion need to be carefully orchestrated, especially in the presence of stark societal fault lines [18]. Neighborhoods of lower socio-economic statuses should not be left to suffer the disproportionate impacts of future pandemics [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This "third way" of social service delivery through grassroots organizing [15] is enticing because it potentially shifts the "burden" of care away from social policy and saves public monies [16] (p. 2139). The rise of apps for neighborhood social networks like Nextdoor in the UK and USA during COVID-19 [17] pointed to its plausibility but also showed that structures for inclusion need to be carefully orchestrated, especially in the presence of stark societal fault lines [18]. Neighborhoods of lower socio-economic statuses should not be left to suffer the disproportionate impacts of future pandemics [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhood attainment, for example, deserves scrutiny when framed as a concrete goal: moving to a neighborhood does not guarantee being able to enjoy its opportunities. Participation in digital neighborhood surveillance and communication platforms like Nextdoor, Ring, and Citizen illustrates the enormous interest and material stakes involved in participatory policing, as well as the community building function of policing (Kurwa 2019;Bloch 2022;Bridges 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The article looks at the history of racial discrimination in US housing and applies theories of social surveillance to Nextdoor. Bloch (2021) takes a cultural geography approach to looking at Nextdoor as an example of social networking apps such as Facebook that purport to mirror or extend existing geographic or social communities. "Such platforms," Bloch concludes, "facilitate the neoliberal off-loading of 'community policing' to those active and engaged residents who work toward the excising of racialized outsiders from otherwise 'inclusive communities'."…”
Section: Racial Profiling Concernsmentioning
confidence: 99%
“…Kurwa (2019) argues that Nextdoor has become a “platform for the surveillance and policing of race in residential space,” leading to the “creation of digitally gated communities.” The article looks at the history of racial discrimination in US housing and applies theories of social surveillance to Nextdoor. Bloch (2021) takes a cultural geography approach to looking at Nextdoor as an example of social networking apps such as Facebook that purport to mirror or extend existing geographic or social communities. “Such platforms,” Bloch concludes, “facilitate the neoliberal off-loading of ‘community policing’ to those active and engaged residents who work toward the excising of racialized outsiders from otherwise ‘inclusive communities’.” The article notes that the first resident who applies to start a new Nextdoor neighborhood often gets to choose the geographic boundaries for defining the “neighborhood.” Once a new community is started, early members are responsible for inviting other to join and to verify that applicants are really residents of the geographic area.…”
Section: The Nextdoor Appmentioning
confidence: 99%